Comparative development and ocular histology between epigean and subterranean salamanders (Eurycea) from central Texas - Tovar, Ruben U.; Cantu, Valentin; Fremaux, Brian; Gonzalez Jr, Pedro; Spikes, Amanda; García, Dana M. (PeerJ, 2021)
The salamander clade Eurycea from the karst regions of central Texas provides an ideal platform for comparing divergent nervous and sensory systems since some species exhibit extreme phenotypes thought to be associated with inhabiting a subterranean environment, including highly reduced eyes, while others retain an ancestral ocular phenotype appropriate for life above ground. We describe ocular morphology, comparing three salamander species representing two phenotypes—the surface-dwelling Barton Springs salamander (E. sosorum) and San Marcos salamander (E. nana) and the obligate subterranean Texas blind salamander (E. rathbuni) - in terms of structure and size of their eyes. Eyes were examined using confocal microscopy and measurements were made using ImageJ. Statistical analysis of data was carried out using R. We also provide a developmental series and track eye development and immunolocalization of Pax6 in E. sosorum and E. rathbuni. Adult histology of the surface-dwelling San Marcos salamander (E. nana) shows similarities to E. sosorum. The eyes of adults of the epigean species E. nana and E. sosorum appear fully developed with all the histological features of a fully functional eye. In contrast, the eyes of E. rathbuni adults have fewer layers, lack lenses and other features associated with vision as has been reported previously. However, in early developmental stages eye morphology did not differ significantly between E. rathbuni and E. sosorum. Parallel development is observed between the two phenotypes in terms of morphology; however, Pax6 labeling seems to decrease in the latter stages of development in E.rathbuni. We test for immunolabeling of the visual pigment proteins opsin and rhodopsin and observe immunolocalization around photoreceptor disks in E. nana and E. sosorum, but not in the subterranean E. rathbuni. Our results from examining developing salamanders suggest a combination of underdevelopment and degeneration contribute to the reduced eyes of adult E. rathbuni.
Keywords: Ocular development; Divergent evolution; Evolution and development; Subterranean salamander